2007
DOI: 10.1111/j.1574-6941.2007.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

N-acyl homoserine lactone-degrading microbial enrichment cultures isolated from Penaeus vannamei shrimp gut and their probiotic properties in Brachionus plicatilis cultures

Abstract: Three bacterial enrichment cultures (ECs) were isolated from the digestive tract of Pacific white shrimp Penaeus vannamei, by growing the shrimp microbial communities in a mixture of N-acyl homoserine lactone (AHL) molecules. The ECs, characterized by denaturing gradient gel electrophoresis analysis and subsequent rRNA sequencing, degraded AHL molecules in the degradation assays. Apparently, the resting cells of the ECs also degraded one of the three types of quorum-sensing signal molecules produced by Vibrio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…EC5 was able to enhance growth of B. plicatilis challenged with V. harveyi mutants lacking functional AI-2 signaling but not those lacking only AHL QS. This indicated that EC5 was capable of degrading 3OHC4HSL and alleviating AHL-mediated growth defects but was unable to inhibit AI-2, and it suggested that probiotic treatment combining AHL-degrading ECs with AI-2-inhibitory bacteria or compounds may be an effective way to protect B. plicatilis during aquaculture (363). More recently, Nhan et al tested ECs from two types of sea bass for their abilities to improve the health of shrimp larvae exposed to waters contaminated with V. harveyi (364).…”
Section: Qsi Success Storiesmentioning
confidence: 99%
“…EC5 was able to enhance growth of B. plicatilis challenged with V. harveyi mutants lacking functional AI-2 signaling but not those lacking only AHL QS. This indicated that EC5 was capable of degrading 3OHC4HSL and alleviating AHL-mediated growth defects but was unable to inhibit AI-2, and it suggested that probiotic treatment combining AHL-degrading ECs with AI-2-inhibitory bacteria or compounds may be an effective way to protect B. plicatilis during aquaculture (363). More recently, Nhan et al tested ECs from two types of sea bass for their abilities to improve the health of shrimp larvae exposed to waters contaminated with V. harveyi (364).…”
Section: Qsi Success Storiesmentioning
confidence: 99%
“…carotovorum (6). AHL-producing and -degrading bacteria coexist in various ecosystems, for example, Penaeus vannamei in shrimp gut and the intestine of Japanese ayu fish (12,25). These bacteria might have different strategies to gain competitive advantages.…”
mentioning
confidence: 99%
“…Enzymes that are able to inactivate AHLs have been discovered in different Gram-negative species belonging to the a-proteobacteria , the b-proteobacteria (Leadbetter and Greenberg, 2000;Lin et al, 2003;Uroz et al, 2003) and the gproteobacteria (Uroz et al, 2003) as well as in some Gram-positive species (Dong et al, 2002;Lee et al, 2002;Uroz et al, 2003). Interestingly, Tinh et al (2007a) very recently isolated AHL-degrading enrichment cultures from the digestive tract of healthy Pacific white shrimp (Penaeus vannamei). The enrichment cultures protected rotifers from the negative effects of an AI-2 non-producing V. harveyi mutant, suggesting that the bacteria interfered with HAI-1-regulated gene expression in vivo.…”
Section: Quorum Sensing In Vibrio Harveyi In Vivo T Defoirdt Et Almentioning
confidence: 99%